Maternal and Fetal Outcomes Among Pregnant Women with Immune Thrombocytopenic Purpura - Güzel, İrfan and Kuyumcuoğlu, Umur and Erdemoğlu, Mahmut (Gynecology Obstetrics & Reproductive Medicine, 2010)
OBJECTIVE: We aimed to report six pregnant women with immune thrombocytopenic purpura (ITP) followed and delivered at our clinic. STUDY DESIGN: This retrospective study was concluded at Dicle University, School of Medicine, Department of Obstetrics and Gynecology, between January 2008 and December 2008. The cases with ITP were referred from the outside centers to our clinic. RESULTS: The mean platelet count of the cases were 70.9 K/UL (18.1-107). The mean age of the cases were 29.4 (20-39), gravidy 3.6 (1-7), and parity 2.6 (0-6). The cases had ITP diagnose before pregnancy, 4 (66.6 %) of the cases had term pregnancy and spontaneous labor, 2 (33.4%) preeclampsia and preterm labor. We induced the labor of these two cases with preeclampsia and delivered vaginally. The other 3 cases had also delivered vaginally, but one of the cases had fetal distress during labor and had cesarean delivery. The babies were healthy, with mean birth weight of 2810 g (1900-3100), 1 minute Apgar score 5 (3-7) and 5 minute 6.6 (5-9). We had transfused 1 unite of trombocyst apheresis solution to one of the case. The cases discharged from the hospital without any complication and day 2-4 days (2.8 days). CONCLUSION: ITP in pregnancy can be a complex and a challenging disease. Mothers with ITP require monitoring during pregnancy and may require intervention with agents to raise the platelet count. With a multidisciplinary approach including obstetrician, hematologist and pediatrician good outcomes can be taken for mother and fetus.